Preparation method and application of Fe-coated Si3N4 heat-conducting wave-absorbing material
By evenly distributing Si3N4 on the iron powder surface and forming Fe@Si3N4 composite thermally conductive wave absorbing material, the problem of insufficient performance of existing wave absorbing materials is solved, and the strong wave absorbing and thermal conductivity is improved, and the filling performance of the material is improved.
Patent Information
- Application Number
- CN202411600638.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
AI Technical Summary
The existing absorbing materials have insufficient performance in electromagnetic wave absorption, especially traditional single-component absorbing materials that are difficult to meet the conditions of impedance matching, and the specific surface area of porous silicon nitride or graphene is large and the filling performance is poor.
Fe@Si3N4 composite thermally conductive and wave-absorbing material is used to uniformly distribute Si3N4 on the surface of iron powder and ball milling and nitriding in a high-temperature atmosphere to form a core-shell structure, which improves the thermal conductivity and wave-absorbing properties of the material.
It achieves strong wave absorption performance and good thermal conductivity, improves the filling performance of the material in the resin matrix, and enhances the reflection and scattering effects of electromagnetic waves.
Smart Images

Figure CN119529566A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of absorbing materials, and in particular relates to a method for preparing a Fe@Si3N4 thermal conductive absorbing material. Background Art
[0002] With the development of electrical, electronic, information and communication equipment, electromagnetic radiation pollution has become a global hazard, which not only causes the performance of electronic equipment to deteriorate, but also seriously endangers people's health. Absorbing materials are usually prepared with polymer resin as the matrix and metal micropowder, ferrite and other absorbers added. In absorbing materials, absorbers are one of the key factors that determine their performance. Traditional absorbers are divided into dielectric loss type materials, magnetic loss type materials and resistive loss type materials. Single-component absorbing materials often have only one absorbing mechanism, which is difficult to meet the impedance matching conditions. The combination of materials with different loss mechanisms can coordinate the characteristics and performance of multiple materials.
[0003] The core-shell structured absorbing material can increase the multiple reflection and absorption of electromagnetic waves by compounding the core particles and shell particles at the micro-nano scale, while giving full play to the synergistic effect of the two, thereby improving the absorbing performance of the material. Silicon nitride is a high-performance ceramic material with excellent high temperature resistance, corrosion resistance and other properties, and is also favored in the field of electromagnetic wave absorption. For example, patent number CN 115449343A provides a silicon nitride absorbing material, which is composited with FeMn@C60 core-shell structure material and porous silicon nitride. The FeMn@C60 core-shell structure material and porous silicon nitride are composited to form a more complex porous material, which increases the number of interfaces and is conducive to improving the absorbing performance of the material. Patent No. CN 115449343 A discloses a method for preparing a phosphoric acid / graphene / silicon nitride coated iron silicon aluminum magnetic powder core, with iron silicon aluminum powder coated with phosphoric acid as the core, and the outer coating layer is composed of graphene, Si3N4 and SiC, irregular Si3N4 covers the graphene surface, wherein SiC is formed at the interface between graphene and Si3N4. A large number of heterogeneous interfaces and conductive micro-networks with a thickness of 0.5μm-0.8μm are formed between Si3N4, SiC and graphene, which improves the wave absorption performance of the magnetic powder core. However, the porous silicon nitride or graphene involved in the above patents have a large specific surface area, and the filling performance in the resin matrix is poor, which is not conducive to the processing and molding of the material. Patent No. CN 104157389 B provides a method for preparing a high-performance soft magnetic composite material, using 50-80nm nano silicon nitride and aluminum nitride dielectric materials to coat iron powder, effectively preventing iron powder oxidation, which is conducive to reducing eddy current losses. The components produced have low eddy current loss, high saturation magnetic induction intensity, high magnetic permeability and resistivity, and high magnetic and mechanical properties. However, the particle size of silicon nitride and aluminum nitride used in the patent is only 50-80nm, the powder particle size is too small, and the filling performance in the resin matrix is poor. At the same time, the outer layer of aluminum nitride is easily hydrolyzed and has poor stability. In order to better improve the application of silicon nitride-based composite materials, this patent has developed a novel Fe@Si3N4 composite thermal conductive wave absorbing material. Summary of the invention
[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a new type of Fe@Si3N4 composite thermal conductive wave absorbing material with low cost and strong absorption, and another purpose is to provide a method for preparing the Fe@Si3N4 composite thermal conductive wave absorbing material. In the Fe@Si3N4 composite thermal conductive wave absorbing material prepared by the present invention, Si3N4 is relatively evenly distributed on the surface of the iron powder, and the application of the Fe@Si3N4 composite thermal conductive wave absorbing material in the organic silicon gasket effectively improves the thermal conductivity and wave absorbing performance of the material.
[0004] A preparation method and application of Fe@Si3N4 thermal conductive wave absorbing material, the specific preparation steps are as follows: Step 1: Place iron powder in an acetic acid solution at a mass ratio of 2:1, stir and react for a period of time, wash the product with anhydrous ethanol, filter, and dry it in a vacuum oven at 40°C to obtain treated iron powder. Step 2: Add distilled water to ZrOCl2·8H2O to prepare an aqueous solution, add silicon powder and stir evenly, then drop ammonia water while stirring, continue stirring for a period of time and then stand for aging to obtain Zr(OH)4. Then wash Zr(OH)4 with distilled water 2-3 times and filter to obtain Zr(OH)4 hydrogel containing silicon powder. Step 3: Place the sample obtained in step 2 in an oven and dry it at 120°C for 24 hours, and then calcine it in an Ar atmosphere to obtain ZrO2-deposited silicon powder. Step 4: The iron powder treated in step 1 and the silicon powder obtained in step 3 are ball-milled at a low speed in a planetary ball mill and placed in a high-temperature atmosphere furnace. A mixed gas of nitrogen and hydrogen is introduced. After reacting at high temperature for a period of time, a Fe@Si3N4 composite thermal conductive and wave absorbing material is obtained.
[0005] In the step (1), the iron powder used is reduced iron powder, and the median particle size D50 is 10-45 μm.
[0006] In the step (1), the mass fraction of the acetic acid solution is 10-20%, the stirring speed is 100-180 r / min, and the reaction time is 15-30 min.
[0007] In the step (2), the concentration of the ZrOCl2·8H2O aqueous solution is 0.15-0.25 mol / L, the mass fraction of ammonia water is 2.0-3.5%, and the pH of the solution is maintained between 9.5-11.5.
[0008] In the step (2), the median particle size D50 of the silicon powder used is 0.2-1 μm.
[0009] In the step (2), the mass ratio of silicon powder to ZrOCl2·8H2O aqueous solution is 1:0.5-2. The coating of ZrO2 is beneficial to reduce the formation temperature of Si3N4.
[0010] In the step (2), the stirring time is 1-3 hours, the stirring speed is 100-150 r / min, and the aging time is 10-15 hours.
[0011] In the step (3), the calcination temperature is 500-800° C. and the calcination time is 4-10 hours.
[0012] In the step (4), the ball milling speed is 100-250 r / min, and the ball milling time is 15-30 min. After ball milling, the fine-grained silicon powder can cover the surface of the iron powder.
[0013] In step (4), the molar ratio of iron powder to silicon powder is 1:0.5-2.
[0014] In the step (4), the mass ratio of nitrogen to hydrogen is 15-20:1-4, and the gas pressure is 0.05-0.15 MPa.
[0015] In the step (4), the reaction temperature is 1000-1300° C. and the reaction time is 8-16 hours.
[0016] In the step (4), the generated Si3N4 is α-Si3N4.
[0017] The synergistic effect principle of the Fe@Si3N4 thermal conductive wave absorbing material of the present invention is as follows: Magnetic loss / dielectric loss Magnetic absorbing materials have a variety of special physical effects and exhibit unique electrical, mechanical and magnetic properties. The magnetic loss material of the present invention is reduced iron powder, because the reduced iron powder has good soft magnetic properties and low coercive force, and low cost is also an important reason for its selection; the dielectric loss material of the present invention is Si3N4, which has the advantages of high thermal conductivity and low specific gravity in addition to good dielectric properties, and the anisotropic drift of the core-shell interface between Si3N4 and Fe is reduced, which is beneficial to improving the compatibility of the coated material with the polymer matrix. The finally prepared Fe@Si3N4 produces interfacial polarization at the core-shell interface, thereby attenuating electromagnetic waves. At the same time, it also produces a frequency resonance effect in the microwave band, naturally modulating the frequency of the incoming electromagnetic waves and causing the incident electromagnetic waves to lose their intrinsic characteristics.
[0018] Beneficial effects of the technology of the present invention: (1) The Fe@Si3N4 thermal conductive absorbing material of the present invention has strong absorbing performance. The porous structure of the reduced iron powder improves the reflection and scattering paths of the incident electromagnetic waves. The coating of the shell Si3N4 not only enriches the loss mechanism of the Fe powder, but also enhances the dissipation of electromagnetic wave energy in the composite absorbing material. (2) The Fe@Si3N4 thermal conductive wave absorbing material of the present invention has a good heat transfer effect. Si3N4 has both high thermal conductivity and good wave absorbing performance, and the heat transfer effect is better. (3) The Fe@Si3N4 thermal conductive and absorbing material of the present invention has good filling performance in the resin matrix. After the Si3N4 is coated on the surface of the Fe powder, the morphology of the material changes from irregular loose and porous to spherical, which effectively improves the filling performance of the material in the resin matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the scanning electron microscope image of blank example 1; Figure 2 This is a scanning electron microscope image of Example 1. DETAILED DESCRIPTION
[0020] In order to better understand the invention, the content of the patent of the present invention is further explained below in conjunction with the implementation examples. However, the content of the patent of the present invention is not limited to the following implementation examples. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work all fall within the scope of protection of the present invention.
[0021] Example 1 Step 1: Place 100 g of 45 μm Fe powder in 50 g of 10% acetic acid solution, stir at a stirring speed of 100 r / min, stir for 30 minutes, wash the product with anhydrous ethanol, filter, and dry in a vacuum oven at 40°C to obtain treated Fe powder. Step 2: Add distilled water to ZrOCl2·8H2O to prepare a solution with a concentration of 0.15mol / L. Add 100g of 1μm silicon powder to 200g of ZrOCl2·8H2O aqueous solution and stir evenly. Then, add 2.0% ammonia water dropwise while stirring at a stirring speed of 100r / min. Continue stirring for 1h and then stand for aging for 10h to obtain Zr(OH)4. Then wash Zr(OH)4 with distilled water 2-3 times and filter to obtain Zr(OH)4 hydrogel containing silicon powder. Step 3: Place the sample obtained in step 2 in an oven and dry it at 120°C for 24 hours, and then calcine it at 500°C in an Ar atmosphere for 10 hours to obtain ZrO2-deposited silicon powder. Step 4: Mill 100 g of the iron powder treated in step 1 and 50 g of the ZrO2-deposited silicon powder obtained in step 3 in a planetary ball mill for 30 min at a rotation speed of 100 r / min. After ball milling, place them in a high-temperature atmosphere furnace, introduce a mixed gas of nitrogen and hydrogen, maintain the gas pressure at 0.05 MPa, and calcine at 1300°C for 16 h to obtain a Fe@Si3N4 composite thermal conductive and wave-absorbing material.
[0022] Example 2 Step 1: Place 100 g of 10 μm Fe powder in 50 g of 20% acetic acid solution, stir at a speed of 180 r / min, stir for 15 min, wash the product with anhydrous ethanol, filter, and dry in a 40°C vacuum oven to obtain treated Fe powder. Step 2: Add distilled water to ZrOCl2·8H2O to prepare a solution with a concentration of 0.25mol / L. Add 100g of 0.2μm silicon powder to 200g of ZrOCl2·8H2O aqueous solution and stir evenly. Then, add 3.5% ammonia water dropwise while stirring at a stirring speed of 150r / min. Continue stirring for 3h and then stand for aging for 15h to obtain Zr(OH)4. Then wash Zr(OH)4 with distilled water 2-3 times and filter to obtain Zr(OH)4 hydrogel containing silicon powder. Step 3: Place the sample obtained in step 2 in an oven and dry it at 120°C for 24 hours, and then calcine it at 800°C in an Ar atmosphere for 4 hours to obtain ZrO2-deposited silicon powder. Step 4: Mill 100 g of the iron powder treated in step 1 and 200 g of the ZrO2-deposited silicon powder obtained in step 3 in a planetary ball mill for 15 min at a rotation speed of 250 r / min. After ball milling, place them in a high-temperature atmosphere furnace, introduce a mixed gas of nitrogen and hydrogen, maintain the gas pressure at 0.15 MPa, and calcine at 1000°C for 8 h to obtain a Fe@Si3N4 composite thermal conductive and wave absorbing material.
[0023] Example 3 Step 1: Place 100 g of 20 μm Fe powder in 50 g of 15% acetic acid solution, stir at a speed of 120 r / min, stir for 20 min, wash the product with anhydrous ethanol, filter, and dry in a 40°C vacuum oven to obtain treated Fe powder. Step 2: Add distilled water to ZrOCl2·8H2O to prepare a solution with a concentration of 0.20 mol / L. Add 100g of 0.5μm silicon powder to 150g of ZrOCl2·8H2O aqueous solution and stir evenly. Then, add 3.0% ammonia water dropwise while stirring at a stirring speed of 150r / min. Continue stirring for 2h and then stand for aging for 10h to obtain Zr(OH)4. Then wash Zr(OH)4 with distilled water 2-3 times and filter to obtain Zr(OH)4 hydrogel containing silicon powder. Step 3: Place the sample obtained in step 2 in an oven and dry it at 120°C for 24 hours, and then calcine it at 600°C in an Ar atmosphere for 8 hours to obtain ZrO2-deposited silicon powder. Step 4: Mill 100 g of the iron powder treated in step 1 and 100 g of the ZrO2-deposited silicon powder obtained in step 3 in a planetary ball mill for 20 min at a rotation speed of 200 r / min. After ball milling, place them in a high-temperature atmosphere furnace, introduce a mixed gas of nitrogen and hydrogen, maintain the gas pressure at 0.10 MPa, and calcine at 1300°C for 10 h to obtain a Fe@Si3N4 composite thermal conductive and wave absorbing material.
[0024] Comparative Example 1 The preparation method of Comparative Example 2 is similar to that of Example 1, except that there is no need to prepare step 1 of Example 1 and no need to add iron powder in step 4 thereof, and Si3N4 powder is directly prepared. The other steps and amounts are the same as those of Example 1.
[0025] Comparative Example 2 The preparation method of Comparative Example 2 is similar to that of Example 1, except that there is no need to prepare step 2 and step 3 of Example 1, and silicon powder is directly used to coat Si3N4 on the surface of the iron powder. The other steps and amounts are the same as those of Example 1.
[0026] Comparative Example 3 Comparative Example 3 is a physical mixture product of Fe and Si3N4 powders with the same specific gravity as the Fe@Si3N4 composite thermal conductive and wave absorbing material in Example 1. The specific preparation method is as follows: 100g of the Fe powder prepared in step 1 and 83g of the Si3N4 powder prepared in comparative example 1 are weighed and placed in a 10L mixer and mixed evenly, wherein the mixing speed is 250r / min and the mixing time is 10min.
[0027] Blank example 1 Blank Example 1 is the treated Fe powder prepared in Step 1 of Example 1.
[0028] The performance test methods and standards are as follows: Wave absorbing performance test: a silicone gasket was prepared with a mass ratio of mixed silicone oil to absorbing powder of 1:3, and its wave absorbing performance was tested by vector network analyzer according to GJB 2038A-2011 standard. The sample size was 300*300mm and the thickness was 2mm. Thermal conductivity test: The silicone gasket was prepared with a mass ratio of 1:3 between the mixed silicone oil and the absorbing powder. The sample size was 26mm*26mm and the thickness was 2mm using a heat flow thermal conductivity tester according to the ASTM D5470-6 standard. Maximum filling amount: The composite thermal conductive absorbing material was continuously added to the 200cp vinyl silicone oil. After preliminary dispersion, it was placed in a vacuum stirring degassing machine with a speed of 600r / min and stirred for 2 minutes until the colloid formed a hard mass and it was difficult to continue filling. The maximum filling amount was obtained. In order to maintain the operability of the colloid, the filling amount of the composite material was reduced during the preparation of the gasket.
[0029] The preparation process of the wave absorbing and thermal conductivity test samples is as follows: 3000g of composite thermal conductive wave absorbing material and 1000g of mixed silicone oil are initially dispersed, and then dispersed evenly using a vacuum mixer for 1.0h; the resulting paste is placed on a release film, calendered according to the set thickness, and vulcanized at 125℃ for 30min to obtain a thermal conductive wave absorbing gasket. The mixed silicone oil system is 100 parts of 200cP vinyl silicone oil + 6.0 parts of side hydrogenated silicone oil + 0.33 parts of acetylene cyclohexanol inhibitor + 0.33 parts of platinum catalyst.
[0030] The performance tests of the Fe@Si3N4 composite thermal conductive and wave absorbing materials prepared in each example are shown in Table 1.
[0031] Table 1:
[0032] From Table 1 and Figure 1 It can be seen that: (1) It can be seen from the scanning electron microscope image of Example 1 that the surface of the reduced iron powder is covered with a relatively dense Si3N4 layer, indicating that Example 1 successfully prepared the Fe@Si3N4 composite thermal conductive and wave absorbing material with a core-shell structure. (2) As can be seen from Table 1, compared with Blank Example 1, the filling number of Example 1 is increased from 550 parts to 1000 parts, and the filling performance is improved by about 81.8%. This is mainly because after Si3N4 coating, the morphology of the material changes from loose and porous to spherical. Compared with Example 1, the filling performance of Example 2 and Example 3 is reduced because Example 2 and Example 3 use Fe with reduced particle size, the specific surface area of the powder increases and the oil absorption value is higher, and the filling performance in the resin matrix is reduced to a certain extent. Comparative Example 3 is a physical mixture product of Fe and Si3N4 powder, a compound of coarse and fine powders. Due to the filling effect of the fine powder, the filling number in the resin matrix is also higher. (3) As can be seen from Table 1, compared with Comparative Example 1, the effective bandwidth (bandwidth of ≤-10dB) of Example 1 is increased from 0.7GHz to 2.9GHz, and the effective bandwidth is increased by about 314%, which shows that the use of reduced iron powder as the core effectively improves the wave absorption performance of Si3N4. Compared with Comparative Example 2, the effective bandwidth of Example 1 is increased by 38%, and the thermal conductivity is increased by 34.6%. The introduction of ZrO2 effectively reduces the nitridation temperature of silicon, increases the nitridation rate of silicon, and promotes the formation of Si3N4. Compared with Comparative Example 3, the effective bandwidth of Example 1 is increased by about 70.6%, which shows that the core-shell structure of Fe@Si3N4 effectively improves the wave absorption performance of the composite material. Compared with Blank Example 1, the effective bandwidth of Example 1 is increased from 0GHz to 2.9GHz, and the thermal conductivity is increased by 228%. The coating of Si3N4 effectively improves the wave absorption and thermal conductivity of the material.
Claims
1. A method for preparing a Fe@Si3N4 thermal conductive wave absorbing material, the specific preparation steps are as follows: Step 1: Place iron powder in an acetic acid solution at a mass ratio of 2:1, stir and react for a period of time, wash the product with anhydrous ethanol 2-3 times, filter, and dry in a vacuum oven at 40°C to obtain treated iron powder; Step 2: Add distilled water to ZrOCl2·8H2O to prepare a ZrOCl2·8H2O aqueous solution, add silicon powder and stir evenly, then drop ammonia water while stirring, continue stirring for a period of time and then stand for aging to obtain Zr(OH)4; then wash Zr(OH)4 with distilled water 2-3 times and filter to obtain Zr(OH)4 hydrogel containing silicon powder; Step 3: The sample obtained in step 2 is placed in an oven and dried at 120° C. for 24 h, and then calcined in an Ar atmosphere to obtain silicon powder deposited with ZrO2; Step 4: The iron powder treated in step 1 and the ZrO2-deposited silicon powder obtained in step 3 are ball-milled at a low speed in a planetary ball mill and placed in a high-temperature atmosphere furnace. A mixed gas of nitrogen and hydrogen is introduced and reacted at high temperature for a period of time to obtain a Fe@Si3N4 composite thermal conductive and wave absorbing material.
2. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (1), the iron powder used is reduced iron powder, and the median particle size D50 is 10-45 μm.
3. The preparation method and application of a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (1), the mass fraction of the acetic acid solution is 10-20%, the stirring speed is 100-180 r / min, and the reaction time is 15-30 min.
4. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (2), the concentration of the ZrOCl2·8H2O aqueous solution is 0.15-0.25 mol / L, the mass fraction of ammonia water is 2.0-3.5%, and the pH of the solution is maintained between 9.5-11.
5.
5. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (2), the median particle size D50 of the silicon powder used is 0.2-1 μm.
6. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (2), the mass ratio of silicon powder to ZrOCl2·8H2O aqueous solution is 1:0.5-2.
7. The method for preparing a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (2), the stirring time is 1-3 hours and the aging time is 10-15 hours.
8. The method for preparing a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (3), the calcination temperature is 500-800° C. and the calcination time is 4-10 hours.
9. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (4), the ball milling speed is 100-250 r / min, and the ball milling time is 15-30 min.
10. The method for preparing a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (4), the molar ratio of iron powder to silicon powder is 1:0.5-2.
11. The method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to claim 1, characterized in that: In the step (4), the mass ratio of nitrogen to hydrogen is 15-20:1-4, and the gas pressure is 0.05-0.15 MPa.
12. The method for preparing a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (4), the reaction temperature is 1000-1300° C. and the reaction time is 8-16 hours.
13. The method for preparing a Fe@Si3N4 thermal conductive wave absorbing material according to claim 1, characterized in that: In the step (4), the generated Si3N4 is α-Si3N4.
14. A method for preparing a Fe@Si3N4 thermal conductive and wave absorbing material according to any one of claims 1 to 12, characterized in that: The Fe@Si3N4 heat-conducting and wave-absorbing powder is used for organic silicon gaskets.
Citation Information
Patent Citations
Preparation method of a high-performance soft magnetic composite material
CN104157389B
Silicon nitride wave-absorbing material and preparation method thereof
CN115449343A
Cited By
Functional network structure design method and application of high-thermal-conductivity wave-absorbing composite material
CN121930612A